Research on RSA and Hill hybrid encryption algorithm. (22nd October 2019) - Yang, Hongyu; Ning, Yuguang; Wang, Yue
A RSA-Hill hybrid encryption algorithm model based on random division of plaintext is proposed. Firstly, the key of Hill cipher is replaced by Pascal matrix. Secondly, session key of the model is replaced by random numbers of plaintext division, and it is encrypted by RSA cipher. Finally, the dummy problem in Hill cipher can be solved, and the model can achieve the one-time pad. Security analysis and experimental results show that our method has better encryption efficiency and stronger anti-attack capacity.